The Effectiveness Analysis of Android Based E-Diagnostic Test Development Program to Identify Level of Student’s Misconception - Mohzana Mohzana; Israwaty Israwaty; Cindy Sandra Lumingkewas; Abdul Tahir; Ilham Arief (Departement of Mathematics Education, 2023)
The purpose of this study is to create an e-diagnostic test application that will help identify students' misconceptions and assess the usefulness of the e-diagnostic test being employed. Based on the use of the e-diagnostic test, this study also attempts to define the profile of students' misconceptions. This type of research is Research and Development (R&D). Tests, questionnaires, interviews, and documentation are the techniques employed. Students are the research participants. An online-based Android test system is the created e-diagnostic application. Work standards, a teacher and student login system, question checking, and question modifying features are all included in the system. With a score of 91.67% and an overall response rate of 80.57%, the validator's validation results demonstrate the high viability of the e-diagnostic test application. 51.32% of students have misconceptions, according to the diagnostic results. The concepts of frequency and centripetal acceleration are both widely misunderstood, with frequency misconceptions ranking highest and lowest respectively.